Does education matter for economic growth? - Michael S. Delgado; Daniel J. Henderson; Christopher F. Parmeter (Institute for the Study of Labor (IZA), 2012)
Empirical growth regressions typically include mean years of schooling as a proxy for human capital. However, empirical research often finds that the sign and significance of schooling depends on the sample of observations or the specification of the model. We use a nonparametric local-linear regression estimator and a nonparametric variable relevance test to conduct a rigorous and systematic search for significance of mean years of schooling by examining five of the most comprehensive schooling databases. Contrary to a few recent papers that have identified significant nonlinearities between education and growth, our results suggest that mean years of schooling is not a statistically relevant variable in growth regressions. However, we do find evidence (within a cross-sectional framework), that educational achievement, measured by mean test scores, may provide a more reliable measure of human capital than mean years of schooling.
Keywords: C14; J24; I20; O10; O40; 330; mean years of schooling; human capital; irrelevant variables; significance testing; nonparametric; Wirtschaftswachstum; Humankapital; Messung; Schulbesuch; Dauer; Bildungsniveau; Schätzung; Welt